The Impact of COVID-19 Outbreak in Italy on the Sustainable Food Consumption Intention From a “One Health” Perspective - Castellini, Greta; Savarese, Mariarosaria; Graffigna, Guendalina (Frontiers in Nutrition, 2021)
Coronavirus disease (COVID-19) is a transmissible illness that was recognized in December 2019 and World Health Organization (WHO) stated a pandemic on 11 March 2020. As no cure has been developed for COVID-19 disease yet, Italy has adopted restrictive measures to avoid the spread of the virus, causing different psychological reactions (e.g., stress, anxiety) that lead people to change lifestyle and in particular the consumer orientation toward food. In addition, the COVID-19 emergency had also affected the Italian economy, causing an 11.3% decrease in GDP (gross domestic product). All these changes gave rise to a sense of instability, but it is known that new possibilities may arise in these situations. In particular, the pandemic could be the turning point to make consumers aware of the close link between human health and the ecosystems, supporting the “One Health” perspective and enhancing the orientation to consumer sustainable food products. However, little is known about how the psychological reactions to COVID-19 emergency have affected the consumers' intention to purchase sustainable food products. In order to answer these questions, a representative sample of 1,004 Italian citizens, extracted by stratified sampling, answered an online survey between May the 12th and 18th 2020. The data were analyzed using ANOVA and contingency tables. The results show that during phase one of COVID-19 disease about 30% of the sample reported that have frequently (often and always) consumed the certified sustainable food products and about 20% of the sample have intention to increase the consumption of them in the next 6 months, percentages that increase among those who feel more vulnerable regarding the risk contagion. Moreover, the psychological impact of the COVID-19 emergency has led to a change in consumers' attitudes, increasing the interest in animal and environmental issues and in human health. These aspects seem to drive the future intention of purchasing sustainable food products. This research highlights how the psychological reactions to the health emergency have changed the consumers' attitudes toward sustainability issues, leading them to follow a more sustainable diet that is recognized as a way to preserve human health, environmental preservation, and animal welfare for present and future generations.